Charismatic Leader on Developing Visionary Pesantren Bidayatul Hidayah in East Java: Profile and Strategy of Dr. KH. Ahmad Musthofa Kamal's Leadership - Muhammad Thoyib (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
The aim of this research is to know the charismatic figure of kyai (Dr. KH Ahmad Musthofa Kamal) and his development strategy of visionary pesantren Bidayatul Hidayah Pasuruan East Java that has competitive value, both in national and international level. Therefore, this research is a qualitative research in the form of field research by using interview, observation and documentation in data collection, and using interactive analysis model of Miles and Huberman in analyzing the findings which consist of data reduction, display data and conclusion. The results of this research concluded: Dr. KH Ahmad Musthofa Kamal is a kyai who since his youth has had a high charisma value around the people in pesantren Bidayatul Hidayah Pasuruan which is characterized by the adherence and high commitment of them on him, including in the implementation of his pesantren education policy; And the strategy of developing visionary pesantren which undertaken by Dr.KH. Ahmad Musthofa Kamal at Pesantren Bidayatul Hidayah includes several things: (a). Improving the quality of education process at Pesantren Bidayatul Hidayah through developing the competence of educator with the scholarship inside and outside country, the provision of competence enrichment such as training of Islamic astronomy and pesantren curriculum, developing education facilities of special boarding's (language, qiroah al-kutub, huffadz lil Qur'an, al-kutub at-turast), and developing visiting teacher program from Middle East-Europe. (b) Improving the quality of pesantren education outcomes in a number of programs, including: strengthening the competence of graduates through entrepreneurship training, and community service, strengthening the network of pesantren graduates as well as strengthening cooperation network among pesantren and world Islamic organization.